2008
DOI: 10.1161/strokeaha.107.494955
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Neurological, Neuropsychological and Sleep-Wake Disturbances After Paramedian Thalamic Stroke

Abstract: Background and Purpose-The clinical features and natural course of paramedian thalamic stroke is poorly known. The aim of this study was to characterize the evolution of neurological, neuropsychological, and sleep-wake deficits after paramedian thalamic stroke. Methods-Forty-six consecutive patients, aged 48.4Ϯ16.6 years, were studied. Fourteen had bilateral, 16 left-sided, and 16 right-sided lesions. Assessment included neurological examinations, estimation of sleep needs, formal neuropsychological tests (nϭ2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
139
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(147 citation statements)
references
References 31 publications
5
139
1
2
Order By: Relevance
“…It is known that recovery is typically poor after a bilateral paramedian thalamic infarction. 15 Our study had several limitations, including the retrospective, noncontrolled study design and the limited number of patients. In addition, rescue treatments might have affected the outcomes in this study.…”
Section: Discussionmentioning
confidence: 97%
“…It is known that recovery is typically poor after a bilateral paramedian thalamic infarction. 15 Our study had several limitations, including the retrospective, noncontrolled study design and the limited number of patients. In addition, rescue treatments might have affected the outcomes in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, PCS patients in general have been shown to have a lower risk of death and a lower burden of disability [12]. The same holds true for several subtypes of PCS such as pontine or thalamic infarction that are considered as having a favorable overall long-term prognosis [13,14]. Consequently, physicians might be cautious to go for thrombolysis especially since PCS symptoms are not adequately represented by the NIHSS as mentioned above [10].…”
Section: Discussionmentioning
confidence: 99%
“…Hermann et al, demonstrated the neurological, neuropsychological, and sleep-wake deficits of 46 paramedian thalamic stroke patients [133]. Oculomotor palsy (76%), mild gait ataxia (67%), deficits of attention (63%), fluency and error control (59%), learning and memory (67%), and behavior (67%) were common in the acute stroke phase.…”
Section: Sleep the Distribution Of Spindles Recovery After Strokementioning
confidence: 99%